ASSOCIATIONS OF LIFESTYLE FACTORS AND 25 HYDROXYVITAMIN D ACCORDING TO COGNITVE STATUS AMONG OLDER ADULTS. (11th November 2018) - Eymundsdottir, H; Chang Gudjonsson, M; Geirsdottir, O; Jonsson, P; Gudnason, V; Launer, L; Jonsdottir, M; Ramel, A
Abstract: Lifestyle can affect vitamin D status in old adults, however, it is not known whether lifestyle is associated with vitamin D in old adults with mild cognitive impairment (MCI) or dementia. In this cross-sectional study we examined associations between lifestyle and serum-25-hydroxyvitamin D (25OHD) among old adults (65-96yrs) with dementia (n=393, 6.8%), MCI (n=550, 9.5%) and normal cognitive status (NCS) (n=4569, 79.2%) from Reykjavik, Iceland. Information on 25OHD, physical activity (PA), cod liver oil, dietary supplements, anthropometrics, smoking and alcohol were collected. 25OHD was significantly lower in demented (53.8nmol/L) and in MCI (55.8nmol/L) than in healthy participants (57.6nmol/L). According to multivariate statistics, cod liver oil (7.1 - 9.1nmol/L, P<0.001) and dietary supplements (4.5–11.1nmol/L, P<0.001) were associated with higher 25OHD in all three groups. However, physical activity (6.6nmol/L, P<0.001), BMI<30kg/m2 (5.2nmol/L, P<0.001), non-smoking (4.8nmol/L, P<0.001) and alcohol consumption (2.5nmol/L, P<0.001) were related to 25OHD in NCS only but not in participants with dementia or MCI. Summing up, it shows that good lifestyle is associated with higher 25OHD in demented (18.2nmol/L), MCI (16.2nmol/L) and healthy participants (32.5nmol/L). Lifestyle is an important determinant of 25OHD among older adults. However, the observed associations were weaker in participants with dementia or MCI and it seems that these old adults are more dependent on dietary and supplementary vitamin D than their healthy counterparts. Since vitamin D has been shown to have extensive positive health consequence further studies are needed in all three cognitive status groups.